Pengaruh Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Kantor Dinas Pekerjaaan Umum dan Penataan Ruang Kabupaten Sikka - Gabriela Delagita; Imanuel Wellem; Paulus Juru (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2025)
This research background was the low performance of employees at the Office of Public Works and Spatial Planning of Sikka Regency, this condition occurs even though they have received adequate support. This research aimed to: (1) determine the description of Employee Performance, Leardership, and Work Motivation; (2) analyze the influence of Leadership and Work Motivation on Employee Performance both partially and simultaneously. The population in this research was 75 employee of the Office of Public Works and Spatial Planning of Sikka Regency. Because the population is limited, this research was conducted by census or saturadet sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression. Hypothesis testing was carried out through the F-test and t-test. The descriptive analysis revealed that the Employee Performance variable met the criteria for being very good, the Leadership variable met the criteria for being good, and the Work Motivation variable also met the criteria for being good. The t-test results indicated that the Leadership variable has a positive and significant effect on Employee Performance, and similarly, the Work Motivation variable has a positive and significant effect on Employee Performance. The F-test results showed that both the Leadership and Work Motivation variables have a significant combined effect on Employee Performance. Additionally, the determination analysis demonstrated that the two independent variables in this research can account for 36.8% of the variation in the rise and fall of Employee Performance at the Public Works and Spatial Planning Service of Sikka Regency.